Speculating on (the) urban (of) art: (un)siting street art in the age of neoliberal urbanisation - Pavoni, A. (Horizontes Antropológicos, 2019)
This paper addresses the current co-optation of street art into an uncritical aesthetic supplement to the process of neoliberal urbanisation, by focusing on its unresolved relation with its own site. This is done in three steps. First, via a perambulating immersion into the complexity of a specific site. Second, via a critical engagement with the form and politics of contemporary street art. Third, via a strategic speculation on the relation between the notions of art, urban and site. Street art’s current impasse, I argue, paradoxically depends on its incapacity to become properly urban. A urban-specific street art, I contend, is not a decorative veneer nor an enchanting disruption to dramatic processes of urbanisation: it is a force-field in which these processes are made visible, experienceable, and thus called into question. The ‘Olympic’ works of JR and Kobra in Rio de Janeiro, and the iconoclastic performance by Blu in Berlin, are used to illustrate and complement the argument.